PENGARUH PENGGUNAAN MODEL PEMBELAJARAN COOPERATIVE LEARNINGTIPE LEARNING TOGETHER (LT) TERHADAP HASIL BELAJAR EKONOMI SISWA KELAS XI - Elsa Sulfiana Sari; Tiara Anggia Dewi (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2018)
The problems in this research are still many students who have not reached the value of KKM or not yet complete the learning result of economy Class XI IPS 3 even semester SMA Negeri 1 Kotagajah academic year 2017/2018 and has not played an active role in the process of learning in the classroom, used by teachers is still not appropriate to optimize student learning outcomes class XI IPS 3 even semester SMA Negeri 1 Kotagajah academic year 2017/2018. So the formulation of the problem is "whether there is influence the use of cooperative learning model type learning together (LT) to the economic learning outcomes of students of class XI even semester SMA Negeri 1 Kotagajah academic year 2017/2018". This research is a Quasi Experimental Design research type of Non-equivalent Control Group Design, in this research there are two classes of experimental class and control class. Population in this research is class XI SMA Negeri 1Kotagajah academic year 2017/2018. Samples of the research are taken class XI IPS 3 as experiment class with number of 30 students and class XI IPS 4 as control class with number of 30 students. The result of research can be seen that tcount>ttabel significant level that is 5%, at 3,79> 1,70 thus Ha accepted. It can be concluded that there is a real influence of the use of cooperative learning model learning type together (LT) to the students' economic learning outcomes of class XI even semester SMA Negeri 1 Kotagajah academic year 2017/2018